Theoretical analysis of the reasonable support capacity based on voussoir beam structure for a given load of the loose body under an extremely close goaf - Ren, Yuqi; Li, Yang; Lei, Xinghai; Ou, Xiangji; Wang, Nan; Li, Guoshuai; Yang, Kunpeng (Frontiers in Earth Science, 2022)
Given the growing popularity of fully mechanized longwall mining, hydraulic shields have emerged as the most crucial pieces of equipment whose rated support capacities are a significant assurance for safe extraction of coal seams. Based on the extraction in the 1,692 panel of the No.9 coal seam in Qianjiaying coal mine, a detailed study of the reasonable shield support capacity under an extremely close goaf was conducted using field measurements, theoretical analyses, and system development. The results show that the ZY4800-13/32 shield employed in the 1,692 panel is unreasonable owing to its large surplus coefficient of support capacity and low support utilization rate. The voussoir beam structure is established for a given load of the loose body to calculate the shield support capacity when the lower coal seam is extracted under an extremely close goaf. The calculated shield support capacity required for the No.9 coal seam was 3,560.03 kN, so the rated support capacity should be 4,000 kN. A calculation and analysis scheme for the shield support capacity under the given load of loose body was developed using a GUI in Matlab, and this scheme was used to examine the influence degrees of the relevant parameters of the immediate roof, main roof, and loose body on the shield support capacity. The thickness of the main roof was found to have the greatest influence on the shield support capacity. Finally, presplitting the main roof was proposed as an effective method for controlling the breaking length and reducing the shield support capacity based on existing research.